Arterial stiffness and central blood pressure, as determined by pulse wave analysis, in rheumatoid arthritis - Klocke, R; Cockcroft, J R; Taylor, G J; Hall, I R; Blake, D R (Annals of the rheumatic diseases, 2003)
Background: Rheumatoid arthritis (RA) is associated with increased cardiovascular mortality for reasons which are insufficiently understood. Chronic inflammation may impair vascular function and lead to an increase of arterial stiffness, an important determinant of cardiovascular risk. Objective: To investigate the augmentation index (AIx) as a measure of arterial stiffness in patients with RA, free of cardiovascular disease or risk factors, by means of a matched cohort pilot study. Method: Patients with a diagnosis of RA, aged 50 years or younger, were screened for the absence of clinical cardiovascular disease and risk factors, such as smoking, hypercholesterolaemia, hypertension, and excessive systemic steroid use. Suitable subjects were assessed by non-invasive radial pulse wave analysis to determine their AIx. These data were compared with those from healthy controls, matched closely for sex, age, mean peripheral blood pressure, heart rate, and height. Results: 14 suitable patients (11 female; mean (SD) age 42 (6) years, mean RA duration 11 (6) years; mean C reactive protein 19 (15) mg/l, no clinical systemic rheumatoid vasculitis) and matched controls were identified. The RA group had a higher mean (SD) AIx and mean (SD) central blood pressure (BP) than the control group: AIx 26.2 (6.7) v 18.9 (10.8)%, p=0.028; mean central BP 91.3 (7.8) v 88.2 (8.9) mm Hg, p<0.0001, by two tailed, paired t test. Conclusions: This preliminary study suggests that RA is associated with increased arterial stiffness and central BP, independently of clinically manifest cardiovascular disease or risk factors. This may contribute to the increased cardiovascular mortality in RA.